Pharmacokinetic and Pharmacodynamic Target Attainment in Adult and Pediatric Patients Following Administration of Ceftaroline Fosamil as a 5‐Minute Infusion - Riccobene, Todd A. (Clin Pharmacol Drug Dev, 2021)
The key pharmacokinetic/pharmacodynamic (PK/PD) efficacy index for β‐lactam antibiotics is the percentage of time that free drug concentrations exceed the minimum inhibitory concentration (MIC) of bacteria during each dosing interval (fT>MIC). Ceftaroline fosamil, the prodrug of the β‐lactam ceftaroline, was initially approved for administration as 60‐minute intravenous (IV) infusions. Population PK analyses comparing exposure and PK/PD target attainment for 5‐minute and 60‐minute IV infusions, described here, have supported ceftaroline fosamil labeling updates to include variable infusion durations of 5 to 60 minutes in adults and children aged ≥2 months. A 2‐compartment disposition PK model for ceftaroline fosamil and ceftaroline was used to predict steady‐state ceftaroline exposures (maximum plasma concentrations [C(max,ss)] and area under the plasma concentration–time curve over 24 hours [AUC(ss,0‐24)]) and probability of target attainment in simulated adult and pediatric patients with various degrees of renal function receiving standard doses of ceftaroline fosamil as 5‐minute or 60‐minute IV infusions. Across age groups and renal function categories, median ceftaroline AUC(ss,0‐24) values were similar for 5‐minute and 60‐minute infusions, whereas C(max,ss) was up to 42% higher for 5‐minute infusions. Both infusion durations achieved >99% probability of target attainment based on PK/PD targets for Staphylococcus aureus (35% fT>MIC) and Streptococcus pneumoniae (44% fT>MIC) at European Committee on Antimicrobial Susceptibility Testing/Clinical and Laboratory Standards Institute MIC breakpoints (1 mg/L and 0.25/0.5 mg/L, respectively). These findings support administration of standard ceftaroline fosamil doses over 5 to 60 minutes for adults and children aged ≥2 months, providing added flexibility to clinicians and patients.